Vibrational and thermal studies of CdSe nanorods. (December 2015) - Das, Sayantani; Banerjee, Sourish; Dutta, Alo; Sinha, T.P.
Abstract: We report the characterization of axial nanorods of cadmium selenide (CdSe), synthesized by soft chemical route using mercapto ethanol as a capping agent. Crystallization temperature of the sample is investigated using differential scanning calorimeter. Kissinger equation is applied to the thermo-grams of differential scanning calorimeter to calculate the thermal activation energy of the sample, which is found to be 1.67 eV. The rod like shape of the sample is confirmed by transmission electron microscope (TEM) and scanning electron microscope (SEM) measurement. The selected area electron diffraction pattern, high resolution TEM image and X-ray diffraction pattern of the sample indicate the cubic structure. The band gap of the sample is obtained using Tauc relation to UV–visible spectrum and found to be 1.98 eV. The photoluminescence (PL) emission spectra of the sample are measured at various excitation wavelengths. The PL spectra appear in the visible region, and the emission feature depends on the wavelength of the excitation. The Raman and infra-red spectra of the samples are analyzed to obtain the vibrational modes and normal modes of the samples.